ANALISIS EFISIENSI DAN SKALA EKONOMIS : STUDI PADA PERBANKAN SYARIAH DI INDONESIA - Suhel Suhel; H.T. Dzulkarnain Amin; Rina Indiastuti; Kodrat Wibowo (Indonesian Journal of Economics and Business, 2012)
This study to analyze cost eficiency at Islamic Banking Industry in Indonesia, by using Stochastic Frontier Approach (SFA), scale economies. The unit analyze of this study is Comercial Islamic Banking/ Bank Umum Syariah (BUS) that has operated at least since 2005. This study is using data panel.The data used is data of quarterly bank unit from financial report of Islamic Banking, The study shows that during 2005 – 2009 period, Islamic Banking Industry has average of eficiency level about 87,15 percent. However, the trend shows that the performance is improving.  It is also that economies of scale is more than 1 too, it meaning that Islamic Banking Industry is in economies of scale condition. Individually, Islamic Banking also shows the same condition.